Structural Recovery of Logged Forests in the Solomon Islands: Implications for Conservation and Management. (June 2021) - Katovai, Eric; Katovai, Dawnie D.; Campbell, Mason; Laurance, Susan G.; Edwards, Will; Laurance, William F.
Much of the lowland tropical forests in the Solomon Islands have been heavily logged. However, little is known about the recovery status of these forests. We examined factors that influenced the recovery of forest structural attributes within 50 years after selective logging on Kolombangara Island in the western Solomon Islands. Twelve study sites—six logged and six unlogged—were identified across the Island, with two logged sites in each of three recovery-time classes: 10, 30, and 50 years after logging. Within each study site, 12 0.1-ha plots were randomly established, and a series of forest attributes measured in each plot. Our results revealed that local logging intensity and soil attributes have stronger influence on forest-structural recovery than do site attributes such as local topography or tree architecture. Furthermore, half a century of regeneration following logging is insufficient to permit full recovery of forest structure. We conclude that logged forests on Kolombangara and possibly across the Solomon Islands may not fully recover structurally before the next logging cycle, in the absence of a policy on re-entry harvesting. The development of such a policy coupled with robust forest-management measures is pivotal to facilitating sustainable logging while supporting biodiversity conservation in the Solomon Islands. This may be the last best hope for saving lowland forests and their biodiversity on this unique tropical archipelago.